Design tourist map’s system using Arc GIS Server: تصميم النظام الخرائطي السياحي باستخدام برنامج ( Arc GIS Server ) - Nourah Bint Salim Al- Kulaib (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2018)
The tourism in the Kingdom of Saudi Arabia has received a great importance and a purposeful vision, where it is a one of the important elements in the Saudi Arabia’s Vision for 2030 and National Transformation Program 2020. Where the vision emphasized the activation of the cultural and heritage tourism and enable everyone to benefit from it all with a facilitates easy. Based on this, I present this study that include a designing a tourist map system using GIS technology that supports a future plans development in various development projects. Where it’s depend on how to design a website that includes tourist data and provide a digital maps of the study area and then published on the Internet using Arc GIS Server software. To do it, this study was based on the technical method of designing and displaying the system on the web. The results which achieved by this study is the displaying of the system in a website through the applied some spatial analysis such as Shortest path Model and Services Area Model, As well as a set of procedural and analytical processes such as (input, manipulation , query, search, and analysis). All of this useful to helps to guide the users to the most important tourist destinations and his services easily in the study area.